2013
DOI: 10.1158/1541-7786.mcr-12-0270-t
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylated GM3 Promotes uPAR-Associated Membrane Molecular Complex to Activate p38 MAPK in Metastatic Melanoma

Abstract: GM3, the simplest ganglioside, regulates cell proliferation, migration, and invasion by influencing cell signaling at the membrane level. Although the classic N-acetylated form of GM3 (NeuAcLacCer) is commonly expressed and has been well studied, deacetylated GM3 (NeuNH 2 LacCer, d-GM3) has been poorly investigated, despite its presence in metastatic tumors but not in noninvasive melanomas or benign nevi. We have recently found that d-GM3 stimulates cell migration and invasion by activating urokinase plasminog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
(75 reference statements)
1
9
0
Order By: Relevance
“…A different study on Metformin’s effect on human epidermoid carcinoma, shows a similar decrease in the activation of MAPK14 33 with a suppressive effect on cancer cell proliferation; another study, shows that Metformin directly decreases the phosphorylation levels of MAPK14 in bovine granulosa cells 35 , a third study shows that Metformin, used in conjunction with gefitinib, decreased levels of MSH2 protein in human lung squamous cell carcinoma, again, through down regulation of MAPK14 34 . Finally, a study on metastatic melanomas shows that activation of MAPK14 by urokinase plasminogen activator receptor (uPAR) clustering on cell surfaces (promoted by d-GM3, a ganglioside) results in the activation of matrix metalloproteinase-2 (MMP-2) 36 which contributes to cell migration and metastasis in cancer cells. This supports our findings with regards to MAPK14 as a putative target of Metformin, and provides some justification for Metformin’s purported anti-cancer activity.…”
Section: Discussionmentioning
confidence: 99%
“…A different study on Metformin’s effect on human epidermoid carcinoma, shows a similar decrease in the activation of MAPK14 33 with a suppressive effect on cancer cell proliferation; another study, shows that Metformin directly decreases the phosphorylation levels of MAPK14 in bovine granulosa cells 35 , a third study shows that Metformin, used in conjunction with gefitinib, decreased levels of MSH2 protein in human lung squamous cell carcinoma, again, through down regulation of MAPK14 34 . Finally, a study on metastatic melanomas shows that activation of MAPK14 by urokinase plasminogen activator receptor (uPAR) clustering on cell surfaces (promoted by d-GM3, a ganglioside) results in the activation of matrix metalloproteinase-2 (MMP-2) 36 which contributes to cell migration and metastasis in cancer cells. This supports our findings with regards to MAPK14 as a putative target of Metformin, and provides some justification for Metformin’s purported anti-cancer activity.…”
Section: Discussionmentioning
confidence: 99%
“…Puujalka et al (2016) reported that from 22 melanoma cell lines, predominant p38 over c-Jun N-terminal kinase signaling results in a VEGF-C high /MITF low phenotype, leading to a highly mobile and metastatic melanoma. GM3, the simplest ganglioside, enhances melanoma metastasis by activating p38 through integrin signaling associated with FAK, PI3K, and Src kinase (Yan et al, 2013). In contrast, the RAS/RAF/MEK/ERK pathway is also important in melanoma progression and metastasis, as evidenced by the clinical significance of B-Raf or MEK inhibitors in treating BRAFmutant metastatic melanoma (Dossett et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Yan et al elucidated mechanism regulating migration and invasion of melanoma cells stimulated with deacetylated GM3. Here, over-expression of the ganglioside caused MMP-2 activation via P38 action, with involvement of lipid membrane raft-associated complexes of uPAR, caveolin-1 and a5b1 integrin, and FAK, PI3K, SRC signaling networks [29]. Tumor-associated gangliosides are also shed to microenvironment and detected in sera of cancer patients.…”
Section: Gangliosides Are Tumor-associated Antigensmentioning
confidence: 90%